Establishment of subcutaneous transplantation platform for delivering induced pluripotent stem cell-derived insulin-producing cells - Hong Thuan Tran; Watchareewan Rodprasert; Irma Padeta; Saranyou Oontawee; Steven dwi Purbantoro; Anatcha Thongsit; Parkpoom Siriarchavatana; Sayamon Srisuwatanasagul; Hiroshi Egusa; Thanaphum Osathanon; Chenphop Sawangmake (PLoS ONE, 2025)
Potential trend of regenerative treatment for type I diabetes has been introduced for more than a decade. However, the technologies regarding insulin-producing cell (IPC) production and transplantation are still being developed. Here, we propose the potential IPC production protocol employing mouse gingival fibroblast-derived induced pluripotent stem cells (mGF-iPSCs) as a resource and the pre-clinical approved subcutaneous IPC transplantation platform for further clinical confirmation study. With a multi-step induction protocol, the functional and matured IPCs were generated by 13 days with a long-term survival capability. Further double encapsulation of mGF-iPSC-derived IPCs (mGF-iPSC-IPCs) could preserve the insulin secretion capacity and the transplantation potential of the generated IPCs. To address the potential on IPC transplantation, a 2-step subcutaneous transplantation procedure was established, comprising 1) vascularized subcutaneous pocket formation and 2) encapsulated IPC bead transplantation. The in vivo testing confirmed the safety and efficiency of the platform along with less inflammatory response which may help minimize tissue reaction and graft rejection. Further preliminary in vivo testing on subcutaneous IPC-bead transplantation in an induced type I diabetic mouse model showed beneficial trends on blood glucose control and survival rate sustainability of diabetic mice. Taken together, an established mGF-iPSC-IPC generation protocol in this study will be the potential backbone for developing the iPSC-derived IPC production employing human and animal cell resources. As well as the potential further development of IPC transplantation platform for diabetes treatment in human and veterinary practices using an established subcutaneous encapsulated IPC-bead transplantation platform presented in this study.